2012
DOI: 10.5539/ass.v8n13p115
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategy Use of Saudi EFL Students in an Intensive English Learning Context

Abstract: This study investigates the type and frequency of language learning strategies used by Saudi EFL students. The subjects were 701 male and female Saudi EFL students enrolled in an intensive English language program at the University of Ha'il. The Oxford Strategies Inventory of Language Learning (SILL) was used with some modifications. The study seeks to extend our knowledge by examining the relationship between the use of language learning strategies (LLS) and gender and proficiency level. The results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
49
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 49 publications
18
49
5
1
Order By: Relevance
“…This finding is in line with results in other studies (Al-Buainain, 2010;Alhaisoni, 2012;C. Chang, 2011;García Herrero, 2013;García Herrero & Jiménez Vivas, 2014;Hong-Nam & Leavell, 2006;Nikoopour et al 2011;Yang, 2007).…”
Section: Overall Usesupporting
confidence: 83%
See 4 more Smart Citations
“…This finding is in line with results in other studies (Al-Buainain, 2010;Alhaisoni, 2012;C. Chang, 2011;García Herrero, 2013;García Herrero & Jiménez Vivas, 2014;Hong-Nam & Leavell, 2006;Nikoopour et al 2011;Yang, 2007).…”
Section: Overall Usesupporting
confidence: 83%
“…Highly proficient learners seem to have a more conscious control of their learning, and they use cognitive strategies in order to develop their language system. These results are not consistent with the studies mentioned before which revealed that proficiency level had a significant effect on the overall strategy use as well as on the different categories (Al-Buainain, 2010;Alhaisoni, 2012;Franco Naranjo et al, 2003;Hong-Nam & Leavell, 2006). However, the findings in the current study are in line with those in the study by García Herrero & Jiménez Vivas (2014) in which high level students employed cognitive strategies significantly more than students in the lowest level.…”
Section: Proficiency Levelcontrasting
confidence: 56%
See 3 more Smart Citations